Income Inequality in Indonesia: Before and during the Covid-19 Pandemic - Tanti Novianti; Dian Verawati Panjaitan (International Journal of Economics and Financial Issues, 2022)
Growth and inequality are economic indicators that are strongly linked to the development process. Regional inequality has long been an issue in Indonesia. This study aims to analyze inequality and economic growth at the city/district level throughout Indonesia before and during the COVID-19 pandemic. It uses secondary data sourced from the Central Statistics Agency (BPS) from 2017 to 2020. The analyzed GRDP and GRDP per capita data consist of 514 cities/districts and 34 provinces. The analytical method used is the Theil Index and Williamson Index (IW). The results revealed that the level of income inequality, calculated based on Theil's Index, was 0.258 in 2019. That value increased to 0.516 in 2020. From 2017 to 2020, the level of inequality in Indonesia increased, followed by inequality within the province itself (within-group), while inequality between provinces (between-group) tended to decrease. The contribution of inequality within the province (within-group) is 53%-63% to the national Theil Index, the rest comes from inequality between groups (between provinces).